Effect of commercial inoculants on the fermentation of alfalfa, corn, forage sorghum, and triticale silages - Bolsen, K.; Ilg, H.; Laytimi, A.; Hart, R.; Chain, V.; Nuzback, L.; Fung, Daniel Y. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fourteen commercial inoculants were evaluated in seven trials using alfalfa, corn, forage sorghum, and triticale silages. Microbial profiles of the inoculants and of the crops differed widely. Viable lactic acid bacteria (LAB) supplied per gram of fresh crop by the inoculants ranged from less than 103 to over 103. Only the alfalfas had 10 or fewer LAB per gram of crop when the forages were treated and as a result, fermentation responses were excellent for those inoculants that supplied 10 or more LAB per gram of treated crop. Corn and triticale underwent a very rapid fermentation rate with very little response to the inoculants. The forage sorghums did not ensile as rapidly as the corn because of their cooler initial temperatures, and most inoculants had little or no effect on the fermentation characteristics. The results of these experiments indicate that if a crop has a high number of LAB, adding more in the form of an inoculant is unlikely to improve the silage fermentation. If a crop has a low number of LAB, it probably will respond to an inoculant, provided the inoculant supplies a large number of viable bacteria.
Keywords: Beef; Inoculant; Alfalfa; Corn; Forage; Sorghum; Triticale; Silage